Endothelial Cell Loss after Phacoemulsification according to Different Anterior Chamber Depths - Hyung Bin Hwang; Byul Lyu; Hye Bin Yim; Na Young Lee (Journal of Ophthalmology)
Purpose. To compare the loss of corneal endothelial cells after phacoemulsification according to different anterior chamber depths (ACDs). Methods. We conducted a prospective study on 135 eyes with senile cataracts. Eyes with nuclear density grades of 2 to 4 were divided into three groups according to ACD: ACD I, 1.5 < ACD ≤ 2.5 mm; ACD II, 2.5 < ACD ≤ 3.5 mm; or ACD III, 3.5 < ACD ≤ 4.5 mm. Intraoperative mean cumulative dissipated energy (CDE) was measured. Clinical examinations included central corneal thickness (CCT) and endothelial cell count (ECC) preoperatively and 2 months postoperatively. Results. There were no significant differences in CDE among the ACD groups (P>0.05). Endothelial cell loss was significantly higher in ACD I than in ACD III in grades 3 and 4 cataract density groups 2 months after phacoemulsification (P<0.05). There were also more changes in CCT in all of the cataract density groups in the ACD I group compared to the ACD II and III groups 2 months postoperatively, but the difference was not statistically significant. Conclusions. Eyes with shallow ACDs, especially those with relatively hard cataract densities, can be vulnerable to more corneal endothelial cell loss in phacoemulsification surgery.